Krisis Model Megachurch Kontemporer: Analisis Struktural, Teologis, dan Eklesiologis - Chris Sorongan; Yoshoa Hartanto; Yosep Heristyo (Lembaga Pengembangan Kinerja Dosen, 2026)
The phenomenon of megachurches represents one of the most significant developments in contemporary Christianity, reflecting shifts in church organizational structures, leadership patterns, and engagement with modern culture. Despite their rapid growth, megachurches have drawn criticism, particularly regarding reliance on charismatic leadership, the prominence of prosperity theology narratives, and the potential weakening of communal dimensions in church life. This study aims to analyze the megachurch phenomenon through an interdisciplinary approach that integrates the sociology of religion and ecclesiological reflection. Employing a qualitative method, this research utilizes literature analysis and a phenomenological approach to understand leadership dynamics and religious practices within large church contexts. The findings indicate that megachurch growth is driven by a combination of charismatic leadership, complex organizational systems, and adaptation to contemporary culture, including digitalization and religious consumerism. However, this model also generates tension with New Testament ecclesiological principles that emphasize participatory community and servant leadership. This study contributes to practical theology by offering an integrative analysis and provides a reflective basis for churches to evaluate their organizational forms and leadership practices in light of foundational theological principles.